Developing Learner Autonomy in Lower-secondary English Classes - Kubátová, Barbora (Univerzita Pardubice, 2023)
This diploma thesis deals with the topic of developing learner autonomy in lower-secondary English classes. The theoretical part defines the concept of learner autonomy and puts it into the broader context of current educational paradigms and approaches to education. Subsequently, it discusses conditions for learner autonomy development and specific strategies and techniques supporting the development of learner autonomy in ELT classes. The practical part contains a case study. The aim of the study is to find out whether and how learner autonomy is being developed in the selected lower-secondary English class.
Rozvoj autonomie žáků v hodinách anglického jazyka na druhém stupni základní školy
Keywords: English language teaching; lifelong learning; learner autonomy; list of features of learner autonomy development; case study; výuka anglického jazyka; celoživotní vzdělávání; autonomie žáka; seznam znaků rozvoje autonomie žáka; případová studie